PENGARUH MOTIVASI INTRINSIK DAN EKSTRINSIK TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI (Studi di Lingkungan Korsatpen Kecamatan Gayamsari Kota Semarang): PENGARUH MOTIVASI INTRINSIK DAN EKSTRINSIK TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI (Studi di Lingkungan Korsatpen Kecamatan Gayamsari Kota Semarang) - Ernawati, Aan (Politeknik Negeri Semarang, 2025)
This research aims to analyze the influence of intrinsic motivation and extrinsic motivation on the performance of teachers with organizational commitment as a mediating variable in elementary school teachers in the Korsatpen environment, Gayamsari District, Semarang City, Central Java. The background to this research is the decline in teacher performance identified from observations from 2020 to 2024, which is influenced by various internal factors such as administrative pressure and lack of innovation factors, as well as external factors. External factors such as the impact of the COVID-19 pandemic and the lack of supervisory support. This research uses Maslow's motivation theory as a theoretical basis, and examines the role of intrinsic (encouragement from within) and extrinsic (external incentives) motivation in improving teacher performance. Organizational commitment is examined as a mediating variable that can strengthen the influence of motivation on performance. The results of the research contribute to identifying strategies for improving teacher performance through strengthening motivation and organizational commitment, thereby impacting on better quality of education in the research environment, especially in the Korsatpen Environment, Gayamsari District, Semarang City, Central Java.